Letter to the Editor of the Ventura County Star from Jane Tolmach with Edits January, 1999 - Jane Tolmach:::::: (1999)
A letter to the editor of the Ventura County Star discussing issues with the Airport Master Plan and opposition to the growth of Oxnard Airport. Includes edits made from the draft.